IMPLEMENTATION OF INTERACTIVE MULTIMEDIA LEARNING BASED ON COGNITIVE LOAD THEORY IN GRADE 5 STUDENTS OF ELEMENTARY SCHOOL - Kurniawati, Rissa Prima; Hadi, Fida Rahmantika; Rulviana, Vivi (Universitas Sebelas Maret, 2018)
Mathematics learning in elementary schools is usually only one-way, teacher-centered, teachers only explain the material, and using existing media in the school,, students just listen and perform tasks given by the teacher. This resulted in students' understanding of math lessons and their learning achievement decreases. Therefore needed a good media that is interactive multimedia learning based on Cognitive Load Theory (CLT). This study aims to describe the application of interactive multimedia learning based on Cognitive Load Theory (CLT) on students of grade 5 SDN 3 Klegen. This research is a qualitative research. The subjects in this study are students of grade 5 SDN 3 Klegen Madiun City. Based on the results of research, on learning by using interactive learning multimedia based cognitive load theory (CLT) is divided into three activities, namely the initial activities, core activities, and closing activities. The average result of the questionnaire score was 88.27%, so the questionnaire was considered good. And also the average value of class 5 SDN 3 Klegen of 78,5 from total 26 students. Students who get grades under the KKM that is 70 as many as 4 students from 26 students. It shows that 84.61%, so it can be concluded that the most students already understand the material of cube and beam volume.